2011
DOI: 10.1108/02656711111132562
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Six Sigma barriers in manufacturing and service organizations

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
62
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 54 publications
6
62
0
2
Order By: Relevance
“…However, when the constructs of LSS readiness were analysed individually, then it was found that working with data and statistics is the only LSS readiness construct that will be affected by the EC and IC significantly, where educational enhancement plays the most significant role as an IC factor to promote working with statistics. This is consistent with the study conducted by Aboelmaged (2011) who has highlighted the knowledge barrier as the key factor in failing to accept change and LSS in SMEs. The result of this research has also been consistent with the argument from Maleyeff et al (2012) who have proposed that undertaking higher education is an enabler for CI practices in any organisation.…”
Section: Research and Practical Implicationssupporting
confidence: 80%
See 3 more Smart Citations
“…However, when the constructs of LSS readiness were analysed individually, then it was found that working with data and statistics is the only LSS readiness construct that will be affected by the EC and IC significantly, where educational enhancement plays the most significant role as an IC factor to promote working with statistics. This is consistent with the study conducted by Aboelmaged (2011) who has highlighted the knowledge barrier as the key factor in failing to accept change and LSS in SMEs. The result of this research has also been consistent with the argument from Maleyeff et al (2012) who have proposed that undertaking higher education is an enabler for CI practices in any organisation.…”
Section: Research and Practical Implicationssupporting
confidence: 80%
“…Although the study presented here only considered seven SMEs within the German manufacturing supply chain it has addressed to some extent the research gap (Atmaca and Girenes, 2013;Thomas and Barton, 2006) of human behavioural factors and their relationship with LSS. Moreover, this research developed more in-depth analysis of the people-related success and failure factors in implementing LSS in SMEs that have already been identified by literature and variety of authors (Prashar, 2014;Aboelmaged, 2011;Choi et al, 2012;.…”
Section: Research and Practical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Perrer et al [23] examined the integration of Lean principles with Six Sigma methodology as a logical approach to continuous improvement and provided a conceptual model for their successful integration. Gamal Aboelmaged's et al [24] study clearly showed that only explicit barriers considerably influenced Six Sigma implementation in relation to dimensions of organizational factors. Vinodh et al [25] and Vinodh and Prasanna [26] identified that the Lean anchorage in the LSS process was rather weak and that it had to be enhanced for improving the effectiveness of LSS approach.…”
Section: Introductionmentioning
confidence: 99%